AN EXAMINATION OF THE APPLICATION OF PSAK-72 TO THE INCOME STATEMENTS OF PT BLUEBIRD Tbk. - Putri, Rajwa Safa Kamilah Noviza; Sari, Sulistiyani Amelia (Jurnal Pijar, 2024)
This study examines the impact of PSAK 72, a financial accounting standard for revenue recognition, on the income of transportation companies in Indonesia, focusing on PT Blue Bird Tbk. PSAK 72, effective January 1, 2020, requires companies to recognize revenue based on the fulfillment of performance obligations in contracts with customers, a shift from previous practices where revenue was often recorded upon service delivery. This transition led to challenges in recognizing revenue from long-term contracts and accounting for variable considerations like discounts or incentives. Through a quantitative analysis of PT Blue Bird's financial performance from 2018 to 2023, the study compares net revenue, gross profit, and net income before and after the standard’s adoption using a paired sample t-test. Results reveal a decline in revenue in the early years of PSAK 72's implementation, with gradual recovery as the company adapted to the new standard. Although the statistical test shows a p-value of 0.055, indicating a near-significant difference, the findings highlight the systematic impact of PSAK 72 on financial reporting. The study provides insights into the challenges and implications of the new revenue recognition model for transportation companies, aiding stakeholders in understanding financial performance changes and informing future strategies